Quantifying the mechanics of locomotion of the schistosome pathogen with respect to changes in its physical environment. Issue 150 (31st January 2019) - Zhang, Shun; Skinner, Danielle; Joshi, Prateek; Criado-Hidalgo, Ernesto; Yeh, Yi-Ting; Lasheras, Juan C.; Caffrey, Conor R.; del Alamo, Juan C.
Abstract : Schistosomiasis is a chronic and morbid disease of poverty affecting approximately 200 million people worldwide. Mature schistosome flatworms wander in the host's hepatic portal and mesenteric venous system where they encounter a range of blood flow conditions and geometrical confinement. However, the mechanisms that support schistosome locomotion and underlie the pathogen's adaptation to its physical environment are largely unknown. By combining microfabrication and traction force microscopy, we developed various in vitro assays to quantify the mechanics of locomotion of adult male Schistosoma mansoni in different physiologically relevant conditions. We show that in unconfined settings, the parasite undergoes two-anchor marching mediated by the coordinated action of its oral and ventral suckers. This mode of locomotion is maintained when the worm faces an external flow, to which it responds by adjusting the strength of its suckers. In geometrically confined conditions, S. mansoni switches to a different crawling modality by generating retrograde peristaltic waves along its body, a mechanism shared with terrestrial and marine worms. However, while the surface of most worms has backward-pointing bristles that rectify peristaltic waves and facilitate forward locomotion, S. mansoni has isotropically oriented tubercles. This requires tight coordination between muscle contraction and substrate friction but gives S. mansoni the ability to reverse its direction of locomotion without turning its body, which is likely advantageous to manoeuvre in narrow-bore vessels. We show that the parasite can also coordinate the action of its suckers with its peristaltic body contractions to increase crawling speed. Throughout this study, we report on a number of biomechanical parameters to quantify the motility of adult schistosomes (e.g. sucker grabbing strength, the rate of detachment under flow, peristaltic wave properties and traction stresses). The new series of in vitro assays make it possible to quantify key phenotypical aspects of S. mansoni motility that could guide the discovery of new drugs to treat schistosomiasis.